High sensitivity detection of the frontier electronic states of CH3NH3PbI3 single crystals by low energy excitation. (11th April 2019) - Yamanaka, Soichiro; Tonami, Ko; Iwashita, Masaki; Yoshida, Koki; Takeuchi, Riku; Ideta, Shin-ichiro; Tanaka, Kiyohisa; Mase, Kazuhiko; Yamada, Koji; Yoshida, Hiroyuki; Nakayama, Yasuo
Abstract: Methylammonium lead triiodide (CH3 NH3 PbI3 ) is an essential material in prototype perovskite solar cells, and its intrinsic electronic structures have been of great interest. In this study, the clean surface of single crystal samples of CH3 NH3 PbI3 was elucidated by X-ray photoelectron spectroscopy, ultraviolet photoelectron spectroscopy (UPS), and photoelectron yield spectroscopy (PYS), and was closely compared with as-prepared single crystal surfaces with considerable native impurities. Low-energy UPS and PYS successfully revealed a presence of electronic states exceeding the Fermi level, which are presumably attributed to electrons transferring from the surface impurities into the conduction band of CH3 NH3 PbI3 .